Odpowiedzi

  • Użytkownik Zadane
2010-03-18T14:28:07+01:00
A. 3(x-3)= 3x -9
b. 5(y +z)= 5y +5z
c. 4(3x - y)= 12x - 4y
d. -2 ( 7 - 4n)= -14 -8n
e. 1/2 (4z +2) = 2z +1
f. - 1/3(6b -3) = 2b +1
g. 0,2 (x - 5y) = 0,2x - (1)y
h. 3(1/3a +1) = (1)a + 3


pozdrawiam
18 3 18
2010-03-18T14:28:10+01:00
3(x-3) = 3x - 9
5(y +z) = 5y + 5z
4(3x - y) = 12x - 4 y
-2 ( 7 - 4n) = - 14 + 8n
1/2 (4z +2) = 2z + 1
- 1/3(6b -3) = -2b + 1
0,2 (x - 5y) = 0,2x - y
3(1/3a +1) = a + 3
4 3 4
2010-03-18T14:28:14+01:00
A. 3(x-3) = 3x-9
b. 5(y +z) = 5y+5z
c. 4(3x - y) = 12x-4y
d. -2 ( 7 - 4n) = -14+8n
e. 1/2 (4z +2) = 2z+1
f. - 1/3(6b -3) = -2b+1
g. 0,2 (x - 5y) = 0,2x-1y
h. 3(1/3a +1) = a+3
4 4 4